The Dynamics of Thrifting Clothing Import Based on Customs Law and Sadd Al-Dzariah in Malang - Tajuddin Nur 'Afas (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
Used imported clothing which is now widespread in Malang apparently does not meet the requirements of the Health Service for sale and purchase. Meanwhile, the aim of this is to ensure the safety and health of consumers so that their physical health is maintained, not only for consumers of imported second-hand clothing but also clothing sellers. This research is empirical juridical with a sociological juridical approach. The data collection method is by conducting interviews and documentation. Then carry out a qualitative descriptive data analysis method to get answers to the problems raised. The aim of the research is to find out the implementation of supervision regarding the prohibition on importing used clothing in Malang, what are the obstacles in carrying out supervision and knowing the implementation of importing used clothing in terms of Islamic Law. First formulation, how to monitor the ban on imports of used clothing in Malang by the Directorate General of Customs and Excise. Second, what are the obstacles in carrying out supervision and how the ban on importing second-hand clothing is implemented from Sadd Dzari'ah's perspective. The results of the research show that with the widespread sale of imported used clothing in Malang, it turns out that there is no action from the Directorate General of Customs and Excise, East Java Region II office in Malang in the form of supervision and the need for coordination between institutions so that this form of supervision and action can be achieved and realized.